Single-cell RNA sequencing reveals the effects of hederasaponin C in the treatment of diabetic nephropathy - Jing Liu; Qian Zhang; Wentong Zhao; Jinan Guo; Yin Kwan Wong; Chunting Zhang; Weijin Qiu; Piao Luo; Junhui Chen; Junmao Li; Xiaoran Li; Hongwei Gao; et al. (Acta Materia Medica)
There is great demand for the development of novel efficient therapeutic strategies or preventative measures to alleviate the life-threatening complications of type 2 diabetes. Hederasaponin C (PB5), a natural product, has been reported to exhibit significant therapeutic effects in various diseases; however, the possible effects and mechanism underlying PB5 in reducing diabetic renal complications have not been comprehensively reported. Here, we investigated the response of murine diabetic models to PB5 treatment using single-cell RNA-sequencing (scRNA-seq) and proteomics. Our findings revealed the dynamic transcriptional changes of renal cells in response to diabetic nephropathy. PB5 alleviated inflammatory injury by partially reducing pathophysiologic processes. In addition, we observed severe glomerular lesions and functional deficiencies, including GBM thickening and podocyte dysfunction, during the progression of diabetes, which were likewise attenuated by PB5. These results provide insight into how PB5 treatment improves diabetic symptoms and possibly serves as a novel protective measure and therapeutic strategy in the treatment of type 2 diabetes.